Efficacy and Safety of Teriflunomide in Multiple Sclerosis across Age Groups: Analysis from Pooled Pivotal and Real-world Studies. (July 2021) - Oh, Jiwon; Vukusic, Sandra; Tiel-Wilck, Klaus; Inshasi, Jihad Said; Rog, David; Baker, Darren P; Pyatkevich, Yelena; Poole, Elizabeth M; Vermersch, Patrick
Background: Evidence suggests that efficacy and safety of disease-modifying treatments for multiple sclerosis may differ with age. We evaluate efficacy and safety of teriflunomide across age subgroups of patients from pooled clinical trials and real-world studies. Methods: Post hoc analyses of patients who received teriflunomide 14 mg in the pooled phase II and III TEMSO, TOWER, TENERE, and TOPIC core and extension studies (n = 1978), and the real-world Teri-PRO (n = 928) and TAURUS-MS I (n = 1126) studies were conducted. Data were stratified by age at study entry: ⩽25, >25 to ⩽35, >35 to ⩽45, and >45 years. In Teri-PRO and TAURUS-MS I, an additional group, >55 years, was assessed. Results: In the pooled core studies, teriflunomide reduced annualized relapse rate (ARR) versus placebo across all ages. Unadjusted ARRs remained low across age groups in pooled extensions (0.18-0.30), Teri-PRO (0.10-0.35), and TAURUS-MS I (0.14-0.35). Baseline Expanded Disability Status Scale scores were higher with age, but stable through core and extension studies (mean increases over 7 years: ⩽25 years, +0.59; >25 to ⩽35 years, +0.46; >35 to ⩽45 years, +0.35; >45 years, +0.81). Across age groups, adverse event (AE) incidences were 78.4% to 90.7% in pooled core and extension studies and Teri-PRO, and 29.2% to 37.7% in TAURUS-MS I; serious AE incidences were ⩽21.3% in all studies. In pooled phase III and Teri-PRO studies, lymphocyte count decreases over 1 year after initiating teriflunomide, and proportions of patients developing lymphopenia, were small across age groups. Conclusions: Teriflunomide efficacy was demonstrated regardless of age. Safety was generally consistent across age groups.